ความสัมพันธ์ระหว่างการกำกับดูแลกิจการกับการจัดอันดับเครดิตองค์กรของบริษัทจดทะเบียนในตลาดหลักทรัพย์แห่งประเทศไทย - นุชชนก ชูแสง (จุฬาลงกรณ์มหาวิทยาลัย, 2007)
The objective of this thesis is to investigate the relationship between the corporate governance and the company credit rating of listed companies in the Stock Exchange of Thailand (SET). The corporate governance consists of 3 areas: (1) the ownership structure and influence, measuring by the proportion of block holder that hold more than 5% ownership level, the proportion of institutional ownership, and the proportion of insiders ownership, (2) shareholders’ rights measuring by the shareholders’ rights score (3) the disclosure and transparency measuring by the disclosure score and the audit firm size, and (4) directors on the board structure measuring by the proportion of independent directors on the board, the CEO duality, and the proportion of directors that hold seat on other firm’ boards. The sample includes listed companies in the SET that to rated company credit rating by TRIS Rating Company Limited for the periods of 2002 – 2006. The logistic regression analysis is employed to analyze the data. As expected at 95% confidence interval, the results show that the corporate governance variables that have a significantly positive relationship to the company credit rating are (1) proportion of institutional ownership, (2) the audit firm size, and (3) the proportion of directors that hold seat on other firm’ boards. The overall classification accuracy of the logistic regression analysis model is 80.50%.